Governance practices and popular legitimacy of the jihadist groups in Mali : a framing analysis of propaganda materials - Anbar, Hajar (2019)
Cross border jihadist activity in Central and Northern Mali continues to pose significant security threat to the region. From 2011 until 2013, most northern parts of the country fell under jihadists control where local populations lived under strict sharia laws. This growing insecurity came as a result of socio economical injustices, particularly towards the northern population mostly composed of Tuareg people. Years of marginalization have led to several rebellions and to the expansion of jihadist factions throughout the country. While the international community acknowledges the need for a swift reaction to eradicate jihadist cells in the region, many activists and researchers call for a more durable solution, one the starts with a holistic understanding of the underlying causes for such groups to gain more power and legitimacy. This study feeds from this rising need for more informed analysis on jihadist groups and aims at challenging the traditional perceptions by recognizing that Jihad is a social movement with social and political claims. Through the leans of social movement theory, this research focused on the collective action frames presented in the jihadist propaganda. The purpose is to consider the social and identity elements it their narrative that might lead to mobilization and support from their target audience. To reach this end, the study identified three Jihadist groups present in Mali through which a set of official propaganda materials was selected to conduct an in-depth thematic analysis. The results make it evident that the three jihadist groups in Mali legitimize their claim and mobilize for support through a discourse filled with social resistance narratives drawn from past and current social struggles.